Penggunaan Pola Produksi Dalam Menentukan Harga Jual Melalui Penerapan Metode Mark Up (Studi kasus pada UMKM Tepung Talas RUSMAN) - Wahyuningsih, Diah; Hasibuan, David HM (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
The main obstacle of the inability of MSMEs to manage and develop businesses is medium or large scale, one of which is efficient production management and the determination of selling prices that are profitable and sustainable in the face of competitors. One of them is the UMKM Tepung Talas Rusman which is a producer of complementary products with a narrow market share and high price competition, so the determination of the amount of production, calculation of production costs and the determination of the right selling price is very decisive. This study aims to determine the application of production patterns, calculation of production costs and determining the right selling price by analyzing the application of the appropriate markup method in order to be able to continue to provide benefits but still able to produce competitive prices. The results of this study show that the pattern of constant production is in accordance with the current condition of MSMEs. This study also shows the calculation of the correct production costs so that an analysis of the determination of the right selling price can be done. The right mark up method with the ability to cover all production costs creates profitability but remains competitive with the ROI Pricing method. Thus MSME TTR can guarantee the profitability and sustainability of its business.